Breast cancer screenings: Does the evidence support the recommendations?. Issue 4 (1st August 2016) - Skorupski, William P.; Wainer, Howard
Abstract : In October 2015, the American Cancer Society announced changes in its recommendations for breast cancer screening. William P. Skorupski and Howard Wainer discuss the evidentiary support for the changes that were made, and the new focus on patient preference Abstract : In October 2015, the American Cancer Society announced changes in its recommendations for breast cancer screening.William P. Skorupski andHoward Wainer discuss the evidentiary support for the changes that were made, and the new focus on patient preference